Mattungka Sapi di Desa Lasiai Kecamatan Sinjai Timur Kabupaten Sinjai: A Case Study on Mattungka Sapi in Sinjai District - Arsyad, Nurfadillah; Amelia, Raines Indah Mutiara; Qayum, Abdul Rahman (Universitas Islam Negeri Alauddin Makassar, 2025)
Profit sharing is a facility that is often used by the community, including the community in Lasiai Village, East Sinjai District, Sinjai Regency. The profit sharing carried out by the people in Lasiai Village is the profit sharing